2007
DOI: 10.1038/sj.onc.1210628
|View full text |Cite
|
Sign up to set email alerts
|

TACC3 depletion sensitizes to paclitaxel-induced cell death and overrides p21WAF-mediated cell cycle arrest

Abstract: Regulators of the mitotic spindle apparatus are attractive cellular targets for antitumor therapy. The centrosomal protein transforming acidic coiled coil (TACC) 3 is required for spindle assembly and proper chromosome segregation. In this study, we employed an inducible RNA interference approach to downregulate TACC3 expression. We show that TACC3 knock-down in NIH3T3 fibroblasts caused aneuploidy, but failed to overtly impair mitotic progression. TACC3 depletion rather triggered a postmitotic p53-p21 WAF pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 42 publications
4
34
0
Order By: Relevance
“…Our studies of TACC3 depletion in murine cells confirm the importance of p21 WAF in preventing severe mitotic abnormalities (23). The p53/ p21 WAF -and retinoblastoma-dependent G 1 checkpoint is compromised in HeLa cells (46), whereas both are functional in the HCT116 cells.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Our studies of TACC3 depletion in murine cells confirm the importance of p21 WAF in preventing severe mitotic abnormalities (23). The p53/ p21 WAF -and retinoblastoma-dependent G 1 checkpoint is compromised in HeLa cells (46), whereas both are functional in the HCT116 cells.…”
Section: Discussionsupporting
confidence: 69%
“…The critical and gene dosage-dependent function of TACC3 in development is further underlined by the impaired chondrocyte differentiation and skeletal malformations in homozygous mutant mice carrying a hypomorphic TACC3 allele (22). Moreover, in the absence of TACC3, murine NIH3T3 fibroblasts enter a G 1 and G 2 cell cycle arrest (23).…”
mentioning
confidence: 99%
“…Accordingly, the p53 target gene p21 WAF , a cyclin-dependent kinase inhibitor, was efficiently induced upon TACC3 depletion, whereas expression of the p53-independent cyclin-dependent kinase inhibitor, p27 KIP , remained unchanged (Supplementary Figure 3a). Furthermore, TACC3 depletion correlated with increased levels of cyclin D1 (Supplementary Figure 3a), which was predominantly confined to the cytoplasm (Schneider et al, 2008 and data not shown) and which is consistent with its function in G 1 arrest and senescence (Kortlever et al, 2006). In contrast, protein levels of the G 2 /Massociated cyclins A and B1 were strongly reduced upon prolonged TACC3 depletion (Supplementary Figure 3a), thus excluding a major contribution of the G 2 checkpoint in the post-mitotic arrest caused by TACC3 depletion.…”
Section: Resultsmentioning
confidence: 94%
“…We have recently shown that TACC3 depletion sensitizes NIH3T3 fibroblasts to PTX-induced cell death, indicating that spindle poisons and downregulation of TACC3 elicit similar signaling pathways in cellular stress responses (Schneider et al, 2008). Indeed, the onset of senescence of two independent TACC3 shRNA-expressing MCF-7 clones could be strongly …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation